Collaboration of Scientists in Agricultural Research Institutes in Nigeria: Implications for Privatisation and Commercialisation of Agricultural Extension - A O Oyedokun (Journal of Agricultural Extension, 2015)
Scientists in the agricultural research institutes are the focus of this study. Through a multistage sampling techniques 172 agricultural scientists from research institutes in 11 agricultural research institutes were selected. Major collaborative extension activities of scientists are with the ADPs. These include diagnostic survey with AÌPs (89 %), training of staff (72 %), organisation of field day /demonstration (63 %) and training of farmers (57 %). Negligible percentage of scientists collaborate with the NGOs in extension' activities; diagnostic survey (11%), training of farmers (13 %) and organisation of field day /demonstration (8 %). Similarly, limited percentage of scientists collaborate with the NGOs in research executed (0.12 %), scientific publications (1.8 %) and joint research proposals (0.5 %). Scientists in the research institutes have strong collaboration with the ADPs (71.08 %), . university (68.42 %) and international agriculture centres (57.89 %). The collaboration with the NGOs is weak (60.40 %) With privatisation there may be further degeneration in collaboration as private extension agencies are more likely to promote their own interests to the neglect of the interests of the public. It is suggested that private and non- governmental organisations should be brought into extension delivery system.